Projecting the future direction of publication patternsUsing text mining (2017)
In this study, text mining techniques were used to identify various research trends in academic journal publications. These techniques were applied to figure out trends in research patterns related to various specialisation areas in Computer Science academic journal articles within a period of two decades. The corpus mined were crawled online, pre-processed and transformed into structured data using filtering and stemming algorithms. The data were grouped into series of word features based on bag of words document representation. Abstracts and the keywords of the articles selected from these journal articles were used as the dataset. It was discovered that the publication trends have changed tremendously from communications and security to artificial intelligence over time.